Pathological features of malignant catarrhal fever in rabbits with a secondary infection of Encephalitozoon cuniculi - Rini Damayanti (Jurnal Ilmu Ternak dan Veteriner, 1995)
Thirty rabbits were used in this study: 22 were infected and eight were used as controls . Fourteen rabbits were inoculated with blood taken from Ongole (Bos indices) cattle or buffalo naturally infected with malignant catarrhal fever (MCF). Another eight rabbits were inoculated with lymphoblastoid cell liras which contain Ovine Herpesvirus-2 (OHV-2), the causal agent of sheep-associated MCF. Various degrees and distributions of histological changes were observed and resembling the lesions developed in MCF. However 17 infected rabbits (77.3%) with non-suppurative meningoencephalitis, eight of them (47.196) were associated with the detection of Encephalhozoon cuniculi histologically .